MEHMET ÂKİF ERSOY’S VIEW OF CONCEPT OF CIVILIZATION İN THE BOOK OF SAFAHAT AND HİS CRİTİQUE OF WESTERN CİVİLİZATİON - Turgay ANAR (Fırat University, 2019)
The concept of “civilization” which is percieved almost same as before, emerges as a conceptual name of “upper status” which colonialist European communities have deemed themselves worthy of, since the second half of XVIII. Century. This concept is important in point of signing the unique development of European communities in many areas as well as in point of emphasising that the other societies are “noncivilized”. Mehmet Akif Ersoy, lives in a region where such ideas and suppositions have stronge effects, determines the problematic situation of Ottoman Empire and Islam civilization. In his poems, he puts into words his suggestions to solve the problem. In some parts of his book namely “Safahat”, we find the comparison of West and East civilizations. Knowing Mehmet Akif Ersoy’s ideas on “civilization”, makes easier to understand his mentality. In case that Safahat is read in chronological order, changes and transformations in Mehmet Akif Ersoy’s views about civilization emerge. In his poems, Akif discusses the idea of taking positive sides of Western civilization to make progress, and this approach can be seen as an answer to discussions on import of civilization. The attack of occupants who represent Western civilization, occupation of Ottoman territories by enemy forces, difficulties which Ottomans struggled with during the beginning of the war of independence, and finally the successes in the battle of Gallipoli cause a lot of modifications and some radical changes in Mehmet Akif’s views on civilization. In this article, all changings in Mehmet Akif’s ideas about civilization are explained by examples.